A Conceptual Sustainability Approach to Tourism Planning and Development in Post-War Bosnia and Herzegovina (BiH) - Alipour, Habib; Dizdarevic, Lejla (Routledge Journals, Taylor & Francis Ltd, 2007)
This research aims to explore the processes of tourism planning and policies in postwar Bosnia and Herzegovina (BiH). For this purpose, a research model has been designed and tested for use in the case of BiH. The main backdrop to this model is based on a new, alternative tourism planning perspective (Tourism planning: a third way?) developed and designed for similar situations (Burns, 2004). The study proceeded by examining the institutions responsible for tourism development through the application of in-depth interviews, content analysis, personal communications, and observation. The findings of the study revealed that although the concept of tourism planning is well understood amongst decision-makers, it has, however, remained a theoretical precept rather than a practice which is implemented. The study has also revealed that the perception of tourism planning and development is devoid of new approaches in respect of the issues of sustainability and community involvement in the decision making process. Therefore, sustainability is not used as an integrated framework, and policies are made without including these two important dimensions, which are at the core of the Third Way model. According to the findings, the present situation can be attributed on the one hand to the political complexity of the economies in transition and, on the other, to the reluctance of the officials to commit themselves to a planning process which involves responsibilities and sacrifices.
Keywords: Evolution